2000
DOI: 10.1016/s0893-133x(99)00142-6
|View full text |Cite
|
Sign up to set email alerts
|

Carbamazepine Suppresses Methamphetamine-Induced Fos Expression in a Regionally Specific Manner in the Rat Brain Possible Neural Substrates Responsible for Antimanic Effects of Mood Stabilizers

Abstract: Carbamazepine (CBZ) has been widely used for treatment of manic states. Because amphetamine produces effects in humans similar to those of idiopathic mania, acute methamphetamine administration could serve as a model of this condition. To elucidate the neurobiological substrates responsible for the antimanic effects of carbamazepine, this study investigated the effects of chronic carbamazepine administration on regional Fos protein expression induced by a single dose of methamphetamine (2mg/kg). Chronic treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 40 publications
2
9
0
Order By: Relevance
“…The low plasma carbamazepine concentrations were comparable to the values obtained by other investigators using a similar dosing regimen (Marangos et al 1985;Lee et al 2000). These low levels are likely a result of differences between the rat and human in the metabolism of these drugs.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The low plasma carbamazepine concentrations were comparable to the values obtained by other investigators using a similar dosing regimen (Marangos et al 1985;Lee et al 2000). These low levels are likely a result of differences between the rat and human in the metabolism of these drugs.…”
Section: Discussionsupporting
confidence: 84%
“…It is unlikely that the reduction in CD151 expression is attributable to the weight loss commonly observed in rats during chronic administration of these mood stabilizers (Baptista et al 1995;Lee et al 2000), as there were no significant differences in weight gain between control and drug-treated animals during the treatment period (Hua et al 2000). Among possible mechanisms that might account for the reduced CD151 expression, altered RNA metabolism through various nuclear events, including rate of transcription, mRNA export, or mRNA degradation, merit further consideration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Valproate doses were arrived at within our group by testing various doses. The carbamazepine dose has been used successfully by other groups (Lee et al, 2000;. Owing to the differences in metabolism between rats and humans, the ratios of carbamazepine and carbamazepine 10,11 epoxide (a primary carbamazepine metabolite) are reversed between the species (Marangos et al, 1985).…”
Section: Animalsmentioning
confidence: 99%
“…Reports have also found that carbamazepine regulates other additional cellular events that may be related to the drug's mood stabilizers efficacy. For example, carbamazepine attenuates stimulated AP-1 DNA binding [243], reduces CD 151 mRNA levels [244], and suppresses stimulated C-fos levels [62,[245][246][247].…”
Section: Carbamazepinementioning
confidence: 99%